2017
DOI: 10.18502/kls.v2i6.1091
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Amylographic Properties of Physically-Modified Sweet Potato Starch

Abstract: In general, native sweet potato starch has inferior characteristics such as it swells easily, does not gel firmly and low paste clarity. The characteristics of native sweet potato starch cause limitation in its utilization. This research aimed to study the effect of physically modified starch on the functional and amylographic properties of native sweet potato starch. The study used a descriptive method with 4 treatments and 2 replications: a) a native sweet potato starch, b) sweet potato modified starch by he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…The conditions of SC‐CO 2 + EtOH extraction, particularly high temperature (86 o C), might cause an increase in molecular mobility and cause structural changes in pea starch that lead to less swelling and a lower pasting viscosity than in nonextracted flour (Garcia‐Solaesa et al, 2019). A similar pattern was determined by Marta and Tensiska (2017) and Kim, Oh, and Chung (2017) for heat‐moisture treated sweet potato starch and brown rice flour, respectively. In contrast, Garcia‐Solaesa et al (2019) reported a similar pasting profile for SC‐CO 2 defatted quinoa grits and native quinoa grits.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The conditions of SC‐CO 2 + EtOH extraction, particularly high temperature (86 o C), might cause an increase in molecular mobility and cause structural changes in pea starch that lead to less swelling and a lower pasting viscosity than in nonextracted flour (Garcia‐Solaesa et al, 2019). A similar pattern was determined by Marta and Tensiska (2017) and Kim, Oh, and Chung (2017) for heat‐moisture treated sweet potato starch and brown rice flour, respectively. In contrast, Garcia‐Solaesa et al (2019) reported a similar pasting profile for SC‐CO 2 defatted quinoa grits and native quinoa grits.…”
Section: Resultssupporting
confidence: 86%
“…Lower peak viscosity of extracted pea flours compared to nonextracted pea flours indicated a reduction in water absorption capacity by the starch granules. As a result, a slow hydration and less swelling along with the amylose leaching occurs during heating (Marta & Tensiska, 2017). The conditions of SC‐CO 2 + EtOH extraction, particularly high temperature (86 o C), might cause an increase in molecular mobility and cause structural changes in pea starch that lead to less swelling and a lower pasting viscosity than in nonextracted flour (Garcia‐Solaesa et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The solubility rate is also related to the presence of soluble amylose as starch component that was released and diffused from the starch granules during the swelling process (Zavareze;Dias, 2011). Previous study about potato starch showed that superheated steam at any temperature (between 100 °C to 160 °C) increased molecule mobility, affecting solubility decline in modified potato starch due to additional bindings among amylose-amylose and amylose-amylopectin interaction (Marta;Tensiska, 2017). Based on Table 1, it is known that modified arrowroot starch has a higher content of resistant starch when compared to the content of resistant starch in natural arrowroot starch.…”
Section: Sweet Bread Texturementioning
confidence: 99%
“…Swelling and WAC were correlated since swelling was influenced by the ability of starch to bind with water molecules through hydrogen bonding. The increased swelling of the starch granules rupture is caused by intermolecular hydrogen bonding in the area of amorphous regions occurring at temperatures below 70°C [48]. The strong correlation of swelling power and WAC is shown in Figure 4.…”
Section: Discussionmentioning
confidence: 93%
“…The reason for blanching was to retain the desirable color of sweet potatoes. The pregelatinized sweet potatoes had a swelling capacity higher than native sweet potatoes, probably because the increase in swelling was related to the increasing amount of amylose and amylopectin leaching of the starch granules [48]. A high amylose content in potato starch and corn starch powders led to very low swelling power as shown in Table 2 on amylose content.…”
Section: Swelling Capacitymentioning
confidence: 97%